2019
DOI: 10.1016/j.celrep.2019.10.076
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Functional Crosstalk between Distinct Bioprocesses through Reciprocal Functional Tests of Genetically Interacting Genes

Abstract: Highlights d Generating a C. elegans inter-bioprocess GI network by comparative GI mapping d Identifying communicator genes between distinct bioprocesses d Ribosomal S6 Kinase/RSKS-1 may be a potential regulator of endocytic recycling transport d RSKS-1 bridges mTOR and insulin signaling by regulating DAF-2 recycling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…However, the mechanism controlling the localization of SMAPs is still not well understood. Here, by using a well-established in vivo membrane trafficking investigation model ( Chen et al, 2018 ; Chen et al, 2019 ; Gao et al, 2020 ; Zhang et al, 2020 ; Yan et al, 2021 ), we showed that the integrity of AP-1 adaptor is necessary for the TGN positioning of SMAP-1. Although we did not specifically identify which AP-1 subunit governs the TGN localization of SMAP-1, our results suggested that in addition to CALM, SMAP-1 underlies an additional clathrin assembly mechanism, enriching the understanding of AP-1/clathrin coat assembly.…”
Section: Discussionmentioning
confidence: 89%
“…However, the mechanism controlling the localization of SMAPs is still not well understood. Here, by using a well-established in vivo membrane trafficking investigation model ( Chen et al, 2018 ; Chen et al, 2019 ; Gao et al, 2020 ; Zhang et al, 2020 ; Yan et al, 2021 ), we showed that the integrity of AP-1 adaptor is necessary for the TGN positioning of SMAP-1. Although we did not specifically identify which AP-1 subunit governs the TGN localization of SMAP-1, our results suggested that in addition to CALM, SMAP-1 underlies an additional clathrin assembly mechanism, enriching the understanding of AP-1/clathrin coat assembly.…”
Section: Discussionmentioning
confidence: 89%
“…Cdc42, a Rho GTPase involved in the regulation of cell cycle, has been reported to modulate the bidirectional transport of COPI vesicles at the Golgi 8 . In addition, an inter‐bioprocess genetic interaction analysis revealed functional connections between intracellular transport and other bioprocesses such as aging 9 . Currently, the regulation of the folding process and homeostasis of many trafficking proteins remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, an inter-bioprocess genetic interaction analysis revealed functional connections between intracellular transport and other bioprocesses such as aging. 9 Currently, the regulation of the folding process and homeostasis of many trafficking proteins remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%